2021
DOI: 10.1002/cb.1925
|View full text |Cite
|
Sign up to set email alerts
|

Customers' social interactions and panic buying behavior: Insights from social media practices

Abstract: The Covid‐19 pandemic led to social distancing and lockdown practices, which increased social interactions and information exchange on social media for timely decision making. This study explores how social practices and social influence generated through social media created panic buying behavior among customers. A social constructionist epistemological position was taken in order to understand the social practice of information sharing and to ask why different meanings were ascribed to Covid‐19 pandemic. Qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(39 citation statements)
references
References 43 publications
1
38
0
Order By: Relevance
“…Hypothetically, it can increase fear by disseminating pictures of the empty shelves and rumors of a shortage of supply (4,10,11,15). Previous studies revealed that mass media and social media have a role in disseminating fear and rumors, which in turn increases erratic behavior like PB (10,12,18,19). Furthermore, it has been reported that fake news on social media demonstrated a strong positive impact on impulse buying (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Hypothetically, it can increase fear by disseminating pictures of the empty shelves and rumors of a shortage of supply (4,10,11,15). Previous studies revealed that mass media and social media have a role in disseminating fear and rumors, which in turn increases erratic behavior like PB (10,12,18,19). Furthermore, it has been reported that fake news on social media demonstrated a strong positive impact on impulse buying (18)(19)(20).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies revealed that mass media and social media have a role in disseminating fear and rumors, which in turn increases erratic behavior like PB (10,12,18,19). Furthermore, it has been reported that fake news on social media demonstrated a strong positive impact on impulse buying (18)(19)(20). In contrast, mass media and social media can minimize PB by reducing public tension and threat and assuring the public that there is a sufficient supply of good.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Such factors may exacerbate people's perceived threats through media communication (Naeem & Ozuem, 2021). The social ampli cation of risk discussed by Kasperson et al (1988) refers to the effects of the broader psychological, social, institutional, and cultural processes affecting people's perception and behavioral responses.…”
Section: Literature Reviewmentioning
confidence: 99%